The state of financial knowledge in the European Union - Maria Demertzis; Luca Léry Moffat; Annamaria Lusardi; Juan Mejino López (Bruegel, 2024)
Only one in two individuals in the European Union, on average, is financially knowledgeable. In response to a 2023 survey containing five questions assessing basic financial knowledge, only half of the respondents answered at least three of the five questions correctly. This represents a low level of financial knowledge and an obstacle for individuals to invest in financial markets. The questions most often answered correctly by respondents measured understanding of inflation and the relationship between risk and return. Only one in five respondents answered correctly a question on the relationship between interest rates and bond prices. Regarding inflation, there is a large difference between the least and most educated respondents in terms of answering the relevant question correctly. Gaps in understanding the concept of inflation are also evident between the youngest (18-24) and oldest respondents (55+) and between the poorest and richest households. A gender gap is present in financial knowledge, with 18 percentage points more men than women answering at least three out of five questions correctly, on average in the EU. Those with greater financial knowledge are less financially fragile in that they can still cover their expenses if there is a sudden loss of income, and are more confident that they will have sufficient funds to sustain themselves during retirement. Countries with higher proportions of people who are financially knowledgeable have higher numbers of people who both save with and borrow from financial institutions, an indication that financial knowledge may improve financial inclusion. All EU countries have, or are in the process of putting together, a national financial literacy strategy. There is an urgent need to roll out these strategies, to monitor progress over time and to establish best practices. Particular attention needs to be given to how financial knowledge interacts with digital skills as financial services are increasingly digitalised. Financial literacy strategies should also help close gender and other gaps in knowledge among vulnerable groups, and should ensure that financial education starts early and in schools.
Keywords: 330